Retinopathy of prematurity among infants admitted to two neonatal intensive care units in Ethiopia - Clare Gilbert; Asrat Demtse; Sadik Taju Sherief; Kalekirstos Taye; Tiliksew Teshome (BMJ Open Ophthalmology, 2023)
Objective This study was conducted to determine the prevalence and risk factors for retinopathy of prematurity (ROP) in two neonatal intensive care units (NICUs) in Addis Ababa, Ethiopia.Methods and analysis A prospective screening survey was conducted from June 2019 to June 2020 in two level 3 public NICUs. Infants with a birth weight (BW) of ≤1500 g or gestational age (GA) of ≤32 weeks and those with a BW of >1500 g and GA of >32 weeks with an unstable clinical course were included. Data on demographic and neonatal characteristics, neonatal and maternal comorbidities, and therapeutic interventions were collected. Logistic regression analysis was used to identify predictors of ROP.Results Two hundred and two infants were included: mean BW: 1658g (range: 700–2400 g) and mean GA: 32.4 weeks (range: 26–34 weeks). 32.2% had any stage of ROP, and 6.4% had Type 1 ROP. Lower BW, smaller GA and total days on oxygen were independent risk factors for severe ROP (Type 1 or worse). All 13 neonates with severe ROP were treated.Conclusion ROP is emerging as a concern in Ethiopia. ROP screening should include neonates with BW of <1800 g or GAs of ≤33 weeks, but further studies are needed in level 2 and private NICUs. Screening guidelines need to be developed and implemented in all hospitals with NICUs.